Analisis Representasi Budaya Lokal pada Iklan GoJek Seri Cerdikiawan (2019) - Natalica Athana (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
Advertising, which was originally a bridge to deliver message, has experienced a shift towards construction of a meaning. In the GoJek Cerdikiawan Advertisement Series (2019), visual signs that construct local culture were found. Especially local culture which is based on values ​​and tradition. Local culture itself describes the reality of life that occurs in people's lives. This analysis uses the semiotic method of Charles Peirce and Roland Barthes which focuses on visual objects in icons, indexes, and symbols of correlation to local culture which will narratemyth. Sources of data derived from visual sign in Cerdikiawan Series advertisement. The results of the study show that some habits carried out by the community have been constructed into culture as a national identity as seen from the reality or events that occur in the society.